A retrospective dosimetric comparison of TG43 and a commercially available MBDCA for an APBI brachytherapy patient cohort. Issue 7 (November 2015) - Zourari, K.; Major, T.; Herein, A.; Peppa, V.; Polgár, C.; Papagiannis, P.
Abstract: Purpose: To compare dosimetry using a contemporary model based dose calculation algorithm (MBDCA) following TG186 recommendations, and the conventional TG43 method in an 192 Ir high dose rate (HDR) accelerated partial breast irradiation (APBI) patient cohort. Methods: Data of 38 APBI patients were studied. Dosimetry for the treatment plans was performed using both the TG43 and TG186 dose calculation methods of the Oncentra Brachy v4.4 treatment planning system (TPS). Analysis included indices of clinical interest for the planning target volume (PTV coverage, dose homogeneity, conformity) as well as dose volume histograms (DVH) for the breast, lung, heart, rib and skin. Significance testing of observed differences between TG43 and TG186 results was carried out and the effect of target location to these differences was studied. Results: Statistically significant differences were observed in the values of clinically relevant DVH parameters for the PTV and the organs at risk (OAR), except for the heart. Differences for the PTV are relatively small (<1% for coverage, on the order of 2% for homogeneity and conformity) with a slight TG43 overestimation except for the dose homogeneity. Percentage differences are larger for the rib and lung (on the order of 4% for Dmax and 5% for V10Gy, respectively) and maximum for the skin (on the order of 6% for D10cc), with a correlation of the observed differences with target location. Conclusion: While the MBDCA option of the TPS appears to improve dosimetric accuracy, differences from TG43 do not appear to warrant dose prescription changes or treatment protocol amendment.. Highlights: Conventional and contemporary dosimetry is compared in an APBI patient cohort. Model based dosimetry appears to improve accuracy. Statistically significant differences are observed in PTV and OAR DVH parameters. Differences are small for the PTV, larger for rib/lung, and maximum for skin. Differences do not warrant dose prescription or treatment protocol changes.